Improving Budgeting and Cost Control Capabilities of MSMEs through Activity-Based Costing and Budgeting Training - Deswanto, Vero (Program Studi Manajemen Fakultas Ekonomi dan Manajemen Universitas Malahayati, 2025)
This community service program aims to strengthen costing, budgeting, and cost control capabilities of Micro, Small, and Medium Enterprises (MSMEs) through an activity-based approach. Many MSMEs experience persistent financial management challenges, including weak cost classification, informal budgeting practices, and limited cost control, which hinder business sustainability and access to financing. The program was implemented through a structured two-day training and mentoring model involving MSME practitioners from security services and rigging project sectors in urban and industrial areas. The training covered cost behavior, cost drivers, activity-based costing (ABC), and activity-based budgeting (ABB), supported by case simulations and group discussions. The results indicate significant improvements in participants’ understanding of cost structures, ability to prepare activity-based operational budgets, and capacity to identify inefficiencies and formulate corrective action plans. This program demonstrates that practical, contextual financial management training can enhance MSME managerial competence, improve cost transparency, and support sustainable business performance at the community level.